NILAI-NILAI DALAM LEGENDA WARATADA DI DESA EIMADAKE KECAMATAN SABU TENGAH KABUPATEN SABU RAIJUA - Oktovian Mira Mangngi; Arnol A. Kolnel; Sanhedri Boimau (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to describe the values contained in the Waratada legend in Eimadake Village, Sabu Tengah District, Sabu Raijua Regency. This study uses a qualitative approach with a descriptive method. The theory used in this research is the theory of literary anthropology. Data collection techniques were carried out through interviews, observation, and documentation. The data analysis technique in this research uses qualitative descriptive analysis, namely by reducing data, presenting data, and drawing conclusions based on research findings. The results of the study indicate that the values contained in the Waratada Legend in the Eimadake Village community, Sabu Tengah District are: (1) Religious Values; (2) Moral Values; (3) Social Values; and (4) Cultural Values. The Waratada Legend not only functions as a folktale but also as a medium for instilling life values that are passed down from generation to generation by the local community.